The novel's patterns manifested in the "exile of the jasmine" by Dr. Abla Alfari - Farhat, Safa Raja (Journal of Humanities & Social Sciences, 2021)
The novel; this literary genre that cannot be defined, derives its mercuriality from its close relations with the variables of society, all that time passes into the unknowns of the future. In spite of this mercurial, and despite the large number of definitions, theorists have succeeded in presenting critical approaches that are somewhat consistent. They also framed the styles of the novel and made it into three central frameworks:-The traditional novel-The modern novel-The new novelThen they classified the novels in their literary criticism; according to these frameworks, based on specific artistic features that distinguished each type of it.Some of the narratives came together for all of these patterns together, and theorists had to explore the artistic features to present a comprehensive critical view, and the novel " Manfa Al- Yasamine" was a successful example of this intermingling.
Keywords: definition; surroundings; variables; events; elements; characters; traditional novel; modern novel; new novel